Relationship Between Risk Management Practices and Investment Decisions in Bank of Kigali, Rwanda - Gedion Alang’o Omwono; Kayumba Annette (Randwick International of Social Science Journal, 2020)
The purpose of this study was to examine the relationship between risk management practices and investment decisions in Bank of Kigali, Rwanda. This study adopted correlational research design. Descriptive statistics include those of the mean, standard deviation and frequency distribution while inferential statistics involves use of spearman’s coefficient correlations. Linear regression was used where ANOVA was carried on each variable. The study found that there was a correlation between liquidity risk management, default risk management and market risk management with performance of the Banks. The study findings indicated that credit risk management (r=0.096, p<0.01), liquidity risk management (r=0.347, p<0.01), market risk management (r=0.506, p<0.01) and operational risk management (r=0.612, p<0.01) on financial performance. It however found that the Banks do not involve experts and consultants in market risk management thus recommendations were made for the Banks to revise their credit risk management policies, open up and share information with other players on market risk thus involve consultants more in their market risk management and to be more proactive than reactive in risk management. The study concluded that, risk management has a positive influence on the investment decisions and that risk monitoring can be used to make sure that risk management practices are in line with proper best practice risk monitoring policies which also helps bank management to discover exposures at early stages and make corrective actions. The study recommended that, Senior management should develop strategies, policies and practices to manage risk in accordance with the Banks risk tolerance and to ensure that the bank maintains sufficient liquidity risk cover.